Phytotoxicity of phenolic acids extracted from palm oil dry solids - Othman, Radziah; Rahmani, Mawardi; Hashim, Azizah (Universiti Putra Malaysia Press, 1997)
A study on the extraction of palm oil dry solids (PODS) was conducted to identify the water-soluble compounds involved in the phytotoxicity of PODS. The aqueous extract of PODS was sequentially partitioned using various organic solvents. Each of the dried extracts was bio assayed for inhibitory activity on the growth of tomato radicles. Maximum inhibition of radicle growth was observed in the diethyl ether extract, resulting in 53.3% growth compared with control. Further separation of the ether fraction using column chromatography resulted in a single toxic fraction, RM10, which caused only 30% radicle growth. The fraction was compared with 14 synthetic phenolic compounds using thin-layer chromatography and was observed to be similar to four of the compounds. Further analysis by high performance liquid chromatography revealed that the RM10 fraction comprised vanillic acid. However, the RM10 fraction was more inhibitory to the growth of tomato radicles than synthetic vanillic acid.